2019
DOI: 10.21608/edj.2019.72681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of silver and copper oxide NANOPARTICLES release from different prosthetic materials incorporated with nanoparticles

Abstract: The purpose of this study was to evaluate the amount of released of silver and copper oxide nanoparticles when they were incorporated in heat cured acrylic resin denture, chemical cured soft liner, and cream type adhesive. Material and methods:A total number of 240 samples were prepared, 80 denture base samples, 80 liner, and 80 adhesives, and 10 samples from each material were free from nanoparticles that act as a control. The remaining samples were divided into two groups: (Group I) contained denture base, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Second: there are a few studies regarding the toxicity, safety, whether the amount of leaching of nanoparticles from acrylic at the concentrations in this study is less than the toxic level or not. However, the amount of nanoparticles release from the denture base is less than the denture liner and the denture adhesive irrespective of the type of nanoparticle (33) . Third: the medium in this study didn't stimulate oral fluid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Second: there are a few studies regarding the toxicity, safety, whether the amount of leaching of nanoparticles from acrylic at the concentrations in this study is less than the toxic level or not. However, the amount of nanoparticles release from the denture base is less than the denture liner and the denture adhesive irrespective of the type of nanoparticle (33) . Third: the medium in this study didn't stimulate oral fluid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles were added to the denture base because it had lower values of nanoparticle release. A comparative study of nanoparticle release from denture base, liner, and adhesive showed that the release was higher in the denture adhesive followed by liner and denture base (32) . Increase release of the nanoparticle may cause systemic toxicity, especially to the CNS (33) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the release of these ions may vary. A study showed that the denture base and adhesive had higher releases compared with the denture liner [ 80 ]. Researchers may explore the controlled and optimum therapeutic release of copper ions for an optimum clinical outcome.…”
Section: Copper Nanoparticles In Dental Materialsmentioning
confidence: 99%